Clove oil as anaesthetic for juveniles of matrinxã Brycon cephalus (Gunther, 1869) - Inoue,Luis Antônio Kioshi Aoki (2003)
Many chemicals have been used as anaesthetics in fish farms and fish biology laboratories to keep the fish immobilized during handling procedures and to prevent accidents and animal stress. In Brazil, tricaine methane sulfonate (MS 222), quinaldine sulfate, benzocaine, and phenoxyethanol are the most common fish anaesthetics used to prevent fish stress during handling, but many side effects such as body and gill irritations, corneal damage and general risks of intoxication have been reported. Clove oil is a natural product proposed as an alternative fish anaesthetic by many researchers and it has been used in many countries with great economic advantages and no apparent toxic properties. In this work, we assessed the suitability of clove oil to anaesthetize matrinxã. Sixty-three juveniles of matrinxã were exposed to seven anaesthetic batches of clove oil (pharmaceutical grade) namely 18, 20, 30, 40, 50, 60, and 70 mg/L. The times to reach total loss of equilibrium and to recover the upright position were measured. Clove oil concentration about 40 mg/L was enough to anaesthetize the fish in approximately one minute and the recovery time was independent in regard to anaesthetic concentration.